Efficient Decomposition of Single-Qubit Gates into V Basis Circuits - Bocharov, Alex; Gurevich, Yuri; Svore, Krysta M. (Physical Review A, 2013)
We develop efficient algorithms for compiling single-qubit unitary gates into circuits over the universal V basis. The V basis is an alternative universal basis to the more commonly studied basis consisting of Hadamard and π/8 gates. We propose two classical algorithms for quantum circuit compilation: the first algorithm has expected polynomial time [in precision log(1/ε)] and produces an ε approximation to a single-qubit unitary with a circuit depth ≤12log5(2/ε). The second algorithm performs optimized direct search and yields circuits a factor of 3 to 4 times shorter than our first algorithm, but requires time exponential in log(1/ε); however, we show that in practice the runtime is reasonable for an important range of target precisions. Decomposing into the V basis may offer advantages when considering the fault-tolerant implementation of quantum circuits.